The potential of Sentinel-1 and Sentinel-2 remote sensing products for monitoring smallholder maize farms in support of the Sustainable Development Goals - Chirima, George (University of Pretoria, 2022)
Thesis (PhD (Geoinformatics))--University of Pretoria, 2021.